2023
DOI: 10.1002/jsfa.12457
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of tilapia skin collagen hydrolysates on ulcerative colitis mice based on metabonomic and16 S rRNAgene sequencing

Abstract: BACKGROUND: Tilapia skin collagen hydrolysates (TSCHs) are the product of enzymatic hydrolysis of collagen, which is mainly extracted from tilapia skin. The components of TSCHs have recently been reported to play a preventive role in dextran sulfate sodium (DSS)-induced ulcerative colitis (UC). However, it has not been illustrated whether TSCHs can prevent against DSSinduced UC via the gut microbiota and its derived metabolites. RESULTS: TSCHs are mainly composed of amino acids, which have similar characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…The solubility of proteins in water depends on the molecules’ size. Proteins with low molecular mass are more soluble in water and easier to absorb in the intestine 29 . The GPC peaks of polypeptides in OP are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubility of proteins in water depends on the molecules’ size. Proteins with low molecular mass are more soluble in water and easier to absorb in the intestine 29 . The GPC peaks of polypeptides in OP are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins with low molecular mass are more soluble in water and easier to absorb in the intestine. 29 The GPC peaks of polypeptides in OP are shown in Fig. 1(A).…”
Section: Characterization Of Opmentioning
confidence: 99%
“…On the other hand, as branched-chain fatty acids, isobutyric and isovaleric acids have a lower abundance and not yet clear mechanism. Chen et al suggested that the main SCFAs elevated but isovaleric acid level reduced did work in preventing colitis [26]. The branched-chain fatty acid may regulate the immune balance and microinflammation of the mucosa of the gastrointestinal tract [27,28], which also affect intestinal motility and clinical syndrome.…”
Section: Discussionmentioning
confidence: 99%